2016
DOI: 10.5894/rgci648
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges of Implementing Integrated Coastal Management and Achieving Sustainability within the Cameroon Coastline

Abstract: More than a decade ago the Food and Agriculture Organization of the United Nations (FAO) published Legal and Institutional Aspects of Integrated Coastal Area Management in National Legislation 1. The preface to that publication pointed out that integrated coastal area management law was a relatively new the field and that few jurisdictions had comprehensive legal frameworks to promote integrated coastal management. The situation has changed dramatically since then. Integrated coastal management (ICM) is now wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The relative poor adaptive capacity of Cameroon is attributable to intrinsic vulnerability (i) increase in PD, (ii) increase in EE, (iii), poor GR, (iv) high Pov and (v) low GDP (CMEF 2005;Nachmany et al 2015;Ngoran et al 2016; this article), all of which are difficult to improve in the short-term. Sustained SED and planning for futures (e.g.…”
Section: Classical and Innovative Adaptation Strategiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The relative poor adaptive capacity of Cameroon is attributable to intrinsic vulnerability (i) increase in PD, (ii) increase in EE, (iii), poor GR, (iv) high Pov and (v) low GDP (CMEF 2005;Nachmany et al 2015;Ngoran et al 2016; this article), all of which are difficult to improve in the short-term. Sustained SED and planning for futures (e.g.…”
Section: Classical and Innovative Adaptation Strategiesmentioning
confidence: 94%
“…Despite the economic significance of Cameroon's coastline, unsustainable utilisation, poor management and the negative impacts of climate change pose serious challenges to its sustainable development (Ngoran et al 2016). Cameroon relies greatly on its agriculture, industries, tourism, and natural resources that are focused upon the 402 km long coastline of the Limbe, Douala and Kribi municipalities.…”
Section: Figurementioning
confidence: 99%
“…Complexity of this nature in coastal governance has implications for resource and livelihood sustainability (Agrawal and Perrin 2009). For this reason, implementing ICM has proven to be a challenge in different parts of the world (Ngoran et al 2016;Cantasano et al 2017;Warnken and Mosadeghi 2018).…”
Section: Coastal Governancementioning
confidence: 99%
“…To face the challenges related to the legal and administrative capacity, it is inevitable to have an agency the has a legal jurisdiction that is expected to fulfill multiple roles and responsibilities such as defining and categorizing the coastal zones, developing and implementing coastal plans, and regulating the development activities in congested zones. Ngoran et al (2016) concluded that, to achieve a beneficial employment of the integrated coastal management, the sectoral lines must be minimized. With respect to the financial capacity, adequate financial resources need to be available for the appropriate planning and application of coastal management strategies.…”
Section: The Iczm Implementation Challengesmentioning
confidence: 99%